Abusive constitutionalism in Poland - on the self-delegitimisation of the judiciary - Kamil Zaradkiewicz (Journal of Modern Science, 2024)
The concept of abusive constitutionalism became widespread in legal scholarship after David Landau's famous publication. The author defines abusive constitutionalism as "the use of constitutional amendment mechanisms to make a state significantly less democratic than it was before" . He refers to actions that make a particular regime "significantly less democratic" . The result, he points out, is to move away from democracy . He pointed to 2013 as examples of this trend - Honduras, Venezuela or Hungary. "De-democratisation" of constitutional mechanisms is also, in my view, relevant from the perspective of the Polish experience, though viewed differently than usually presented in the political debates. It turns out that democratic mechanisms and their implementation are undermined by those judiciary representatives who, simultaneuosly, accuse the authorities introducing solutions in line with democratic principles of violating the rule of law.